(untitled) (Diametros, 2013)
The paper contains a philosophically examinesation of the notion of the common good. The major point argued is that the common good, contrary to the way it isits traditionally definedition in political philosophy, need not be communitarian alone, itbut couldan also be liberal. The paper juxtaposes the normative liberal idea of liberty to the communitarian notion of the common good. The conclusion is that the liberal notion of liberty couldan serve the common good, especially in a liberal society. Theis idea of liberal liberty is not antithetical to the common good.